2007
DOI: 10.1161/circulationaha.107.696823
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Endothelial Function in School-Aged Nonobese Children

Abstract: Background-Obstructive sleep apnea (OSA) in children is associated with cardiovascular morbidity such as systemic and pulmonary hypertension. However, it remains unclear whether endothelial dysfunction occurs in pediatric OSA and whether it is reversible on effective treatment of OSA. Methods and Results-Consecutive nonobese children (aged 6 to 11 years) who were diagnosed with OSA after overnight polysomnography and control children matched on the basis of age, gender, ethnicity, and body mass index underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(149 citation statements)
references
References 41 publications
4
132
2
9
Order By: Relevance
“…A striking finding is that in non-obese children with OSAS, REM-related OSAS is more frequently detected (19). In studies performed on children with OSAS, the development of morbidities as metabolic dysfunction, hypertension, vascular endothelial dysfunction, systemic inflammation, and increased oxidative stress have been demonstrated (30)(31)(32)(33). Observations gathered from children display their importance in the definition of REM-related events in adults.…”
Section: Rem-related and Non-remrelated Osas (N=329)mentioning
confidence: 99%
“…A striking finding is that in non-obese children with OSAS, REM-related OSAS is more frequently detected (19). In studies performed on children with OSAS, the development of morbidities as metabolic dysfunction, hypertension, vascular endothelial dysfunction, systemic inflammation, and increased oxidative stress have been demonstrated (30)(31)(32)(33). Observations gathered from children display their importance in the definition of REM-related events in adults.…”
Section: Rem-related and Non-remrelated Osas (N=329)mentioning
confidence: 99%
“…Подобные изменения были выявлены у детей, при-чем отмечалось улучшение функции эндотелия на фоне лечения апноэ сна [59]. Показано, что ожи-рение и наличие обструктивного апноэ сна в препу-бертатном возрасте оказывают сочетанное негатив-ное воздействие на состояние эндотелия сосудов [60].…”
Section: российский вестник перинатологии и педиатрии 4 2016unclassified
“…Defining the outcomes of importance in evaluating treatments in children with OSA is itself worth considering. Studies have identified and reported post-therapy AHI and/or oxygen saturation and other respiratory measures, sleep EEG analysis such as sleep stages, spindles, arousals, and spectral analysis, various neurocognitive and/or behavioral measures, parental and teacher report of improvement or satisfaction, academic performance, and more recently serologic markers [5][6][7][8] such as C-Reactive Protein, and other physiological tests [7,9] as evidence of treatment effect. Interestingly, these outcomes do not necessarily show symmetry at baseline or in response to intervention ; for example, in children treated by adenotonsillectomy, hyperactivity, inattention, cognitive function, and other neurobehavioral morbidities all tended to be improved a year after treatment, but little correlation has been seen between some of these variables and polysomnographic measures before or after surgery, though esophageal pressure monitoring as a more sensitive measure of breathing abnormalities may offer some promise in this regard [10,11].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%